Pertumbuhan Ekonomi Indonesia Perspektif Ekonomi Islam: Peran Inflasi, Pengeluaran Pemerintah, Hutang Luar Negeri dan Pembiayaan Syariah - Eny Widiaty; Anton Priyo Nugroho (ITB AAS INDONESIA Surakarta, 2020)
Economic growth is a fundamental indicator in assessing economic performance. In assessing the economic growth, it can use several important variables such as Inflation, Government Consumption Expenditure, Foreign Debts, and Sharia Finance. In turn, this research aims to analyze the impacts of these variables on the economic growth in Indonesia (Quarter I – Quarter IV) in the period of 2011-2018. The Error Correction Model used in the analysis method. The results of the analysis showed that the variable inflation in the long-term harmed economic growth; while, in the short-term, the level of inflation had a positive impact on economic growth. Meanwhile, the variable of Government Consumption Expenditure had a negative contribution to economic growth. Furthermore, foreign debt in the long term hurt economic growth, but for the short term, it could bring the positive one. Variable of Sharia finance showed a good result both in the short term and in the long term with a negative correlation with economic growth in Indonesia. However, all variables of inflation, Government Consumption Expenditure, foreign debts, and sharia finance simultaneously had an impact on National Economic Growth.